1986
DOI: 10.1136/bmj.293.6541.234
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and reproducibility of a new contrast clearance method for the determination of glomerular filtration rate.

Abstract: A new method for determining the glomerular filtration rate was analysed prospectively. The method uses an x ray fluorescence technique to measure disappearance from the plasma of injected non-ionic iodinated contrast media. Eighty seven patients were studied. Fifty four had an intravenous dose of 100 ml iohexol (Omnipaque) and 33 had 50 ml iohexol. Clearances of chromium-51 labelled edetic acid ("Cr-EDTA) were measured simultaneously. In the patients given 100 ml iohexol there was excellent correlation with 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 8 publications
1
34
0
1
Order By: Relevance
“…(20) in an extensive study comparing XFA contrast medium clearance at three dose levels with simultaneously performed "Cr-EDTA clearance, reported slightly lower, 0.69-0.90, correlation coefficients.…”
Section: Discussionmentioning
confidence: 95%
“…(20) in an extensive study comparing XFA contrast medium clearance at three dose levels with simultaneously performed "Cr-EDTA clearance, reported slightly lower, 0.69-0.90, correlation coefficients.…”
Section: Discussionmentioning
confidence: 95%
“…It has been demonstrated that the plasma clearance of contrast media can be determined with x-ray fluorescence analysis after a single injection of contrast medium (2,10,11). Clearance is then calculated from the late part of the plasma contrast medium concentration curve (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The total plasma clearance after a single injection of contrast medium can readily be determined with the aid of x-ray fluorescence analysis (1, 2, 8-1 I ) and calculated by the same procedure as for single injection "Cr-EDTA clearance (2,3,10,11).…”
mentioning
confidence: 99%
“…Iohexol measurement is also pretty stable at room temperature and at -20°C (Krutzen et al, 1984;O'Reilly et al, 1988). Measurement of iohexol by XRF method is less validated and probably less performing, especially in low plasma concentrations (O'Reilly et al, 1986;Back & Nilsson-Ehle, 1993;Effersoe et al, 1990;Brandstrom et al, 1998;Aurell, 1994). We will not discuss into details the other methods for measuring iohexol: capillary electrophoresis (Shihabi & Constantinescu, 1992) and mass spectrometry (Lee et al, 2006;Annesley & Clayton, 2009;Denis et al, 2008;Stolz et al, 2010).…”
Section: Physiological and Analytical Datamentioning
confidence: 99%